Sustainability indicators to study grasslands - Lok, Sandra (Cuban Journal of Agricultural Science, 2010)
The study of the main sustainability indices was conducted in grassland agroecosystems. The concepts of sustainability and grassland systems were dealt with thoroughly. Some elements were analyzed favoring the sustainable use of grasslands and referring to the importance in the use of indices as monitoring and control measurements of the functioning of these systems. Also, basic criteria were shown to select the indices, and the state-of-the-art in this subject was considered. It was concluded that the subject related to the study and selection of sustainability indices is of great attraction and interest worldwide. The indices should be trustworthy, easy to measure, and repeatable in time. For a grassland system may be sustainable, dynamic balance should be attained between its constituents in a way that the adequate productivity, the resiliency, the equity, and the stability in the economic, social, and ecological dimensions are accomplished. Studies on grasslands have noted, as principal plant indices, the botanical composition, the plant coverage, the presence of foreign and native species, the biomass production, and the biomass availability. In the soil, they noted the content of organic matter, the edaphic biota (macrofauna, microfauna, and mesofauna), the stability of the aggregates, the texture, and the content of humidity and nutrients. In the animal component, the total production and per animal and the grazing pressure are some of the indices most commonly reported in the literature. It was concluded that the determination of indices should be specific for each type of grassland. Further studies on several types of grasslands are recommended, as well as the spread of the outcomes obtained. Key words: indices, sustainability, grasslands.